An interpretive assessment of athlete`s perceptions: The influence of rule changes on the psychological demands of pole vaulting - Lobinger, B. H.; Solomon, G. B. (Athletic Insight - The Online Journal of Sport Psychology, 2010)
The sport of pole vaulting is a relatively new endeavor in the world of track and field. There is a great deal of consensus regarding the element of risk associated with this event. A series of rule changes were enacted in the pre-Olympic year 2003 involving facilities, procedures, and judging. A significant procedural change involved reducing the time limit in preparation for the vault; preparation for the takeoff run was reduced from 90 to 60 seconds. The purpose of the study was to assess the influence of the rule changes on top athletes` perceptions and behaviors. Fifteen elite German pole vault athletes were interviewed regarding the perceived effects of the rule changes on preparation and performance. The majority of athletes reported that the time limit required them to alter their preparation and performance routines. The results further suggest that male athletes feel more disturbed by the rule changes than female athletes. These results are discussed in light of previous research on the influence of performance routines and implications for coaches and athletes.